Case Report: Small Bowel Obstruction Owing to Self-Anchoring Barbed Suture Device After TAPP Repair - Zheng, Longbo; Yin, Xiangyi; Liu, Huasheng; Wang, Shouguang; Hu, Jilin (Frontiers in Surgery, 2021)
Groin hernioplasty is the most performed intervention in the adults worldwide, the minimally invasive inguinal hernia repair techniques widely used by surgeons today are transabdominal preperitoneal patch plasty (TAPP) and total extraperitoneal patch plasty (TEP). We report a 62-year-old man with bowel obstruction caused by the use of self-anchoring barbed suture to close the peritoneum 3 days after TAPP. Surgeons using the barbed suture should be alert to this possibility when encountering this complication of intestinal obstruction, so as to avoid more serious consequences.